Nurses’ Experiences of Caring for Patients with COVID-19 - yongchaiyoot, pimwimon; Oumtanee, Areewan (Journal of The Royal Thai Army Nurses, 2023)
The purpose of this study is to describe nurse’s experiences of caring for patients with COVID-19. Martin Heidegger was applied as a research methodology. Study informants were 15 nurses working at COVID-19 units in a selected hospital, during January 2021-July 2022. In-depth interview with tape-record with fieldnote were use as data collection method. All interviews were transcribed verbatim and analyzed by using content analysis of van Manen’s method, Verify the reliability of the information according to the methods of Lincoln and Guba The findings of nurse’s experiences of caring for patients with COVID-19 consist of 7 themes including 1) providing physical comfort to patients 2) giving psychological support to fight with vigorous disease 3) requiring closed monitoring due to unpredictable changes of signs and symptoms 4) providing things as patients’ needs, 5) paying attention of patients’ health coverages 6) negotiating for assistance with health related department and 7) taking care the last moment of patient’s life with other health related